A Novel Approach of Targeted Immunotherapy against Adenocarcinoma Cells with Nanoparticles Modified by CD16 and MUC1 Aptamers. (11th October 2015) - Yu, Lianyuan; Hu, Yan; Duan, Jinhong; Yang, Xian-Da
Abstract : Mucin 1 (MUC1) is a potentially important target of cancer therapy, being a glycoprotein that is overexpressed on cell surface of many types of adenocarcinomas, including breast, ovarian, colon, lung, and prostatic cancers. Several MUC1-targeted drug delivery systems have been developed and reported, but mobilizing natural killer cells (NK) to fight against MUC1-positive tumor has not been attempted. In this study, we introduced a novel amphipathic nanoparticle (NP) for enhancing the NK cytotoxicity to MUC1-positive cancer cells. The amphipathic NP had CD16 and MUC1 aptamers on its surface and was designed to bind with both the CD16-positive NK cells and the MUC1-positive tumor cells and pull the two types of cells close to each other. The fabricated amphipathic NP had an average size of 574 nm. The aptamers' conjugation with the NP was confirmed by DNA hybridization experiments. Dark-field microscopy revealed that the amphipathic NP could recruit more NK cells to the vicinity of MUC1-positive cancer cells. Additionally, the amphipathic NP significantly enhanced the NK cytotoxicity to MUC1-positive cancer cellsp < 0.01, but not that to the MUC1-negative control cells. The results suggest that NK cells may potentially be mobilized to selectively fight against MUC1-positive cancer cells.